Keterkaitan Media Pembelajaran Digital dalam Meningkatkan Motivasi dan Hasil Belajar Siswa Kelas IV SD - Yarisda Ningsih; Nur Azmi Alwi; Alya Suci Rahmadani; Elmemi Wagira; Qonita Mutiara (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study explores various factors relating to the implementation of digital learning tools intended to inspire excitement among fourth-grade students. The motivation for this research stems from the noticeable lack of student participation, which is associated with the limited availability of diverse and stimulating educational resources. It is proposed that the adoption of digital educational tools can create a more engaging and relevant learning environment, subsequently boosting students' drive to learn. The investigation follows a qualitative framework, utilizing a case study method where data is gathered through the observation and documentation of fourth-grade students in elementary education. Findings from this research indicate that the incorporation of digital educational materials, including teaching videos, interactive assessments, and online learning platforms, markedly enhances students’ engagement and participation in their educational experience. The utilization of digital content fosters a more vibrant classroom atmosphere, aiding students in grasping the material more effectively. In summary, digital educational resources have the potential to significantly improve student motivation, especially within primary schooling.